(untitled) (Global Journal of Management and Business Research, 2023)
Abstract- Self-Initiated Expatriates SIEs are individuals who independently choose to move to a foreign country such as the United States without seeking help from external sources during the relocation process A US Self-Initiated Expatriate is an individual who autonomously pursues employment or other opportunities in the United States with the objective of establishing permanent residency without relying on the support of any organization or agency The objective of this research was to identify key factors related to self-initiated expatriation in the United States The objective was achieved by conceptualizing the following factors Economic Factors Professional Development Lifestyle Cultural Factors and Family Factor The study utilized a quantitative research methodology to investigate five hypotheses with the objective of identifying the factors that contribute to self-initiated expatriation in the United States